Miniature single-sideband subharmonically-pumped 60 GHz direct upconverter in a uniplanar GaAs pHEMT technology using inductive and capacitive loading techniques. Issue 3 (23rd April 2013) - Hettak, Khelifa; Ross, Tyler N.; Irfan, Nazish; Cormier, Gabriel; Yagoub, Mustapha C. E.; Morin, Gilbert A.; Wight, Jim S.
Abstract : This paper presents a novel, compact, single-sideband (SSB) subharmonically-pumped (SHP) direct upconverter developed in a uniplanar 0.18 μm GaAs technology. A total of 100 MHz in-phase and quadrature signals directly modulate the second harmonic of a 30 GHz carrier signal, producing a 60.1 GHz output. Two pairs of antiparallel diodes reduce feed-through of the 30 GHz local oscillator (LO) signal to the mixer's RF output. Novel structures patterned in the center conductor of a coplanar waveguide (CPW) provide matching and size-reduction simultaneously. The 2.1mm 2 circuit also uses a miniaturized Wilkinson divider based on asymmetric coplanar stripline and a standard CPW 90° coupler. The SSB SHP direct upconverter exhibits a conversion loss of 10 dB, a lower-sideband rejection of 15 dB and 2fLO suppression of approximately 25 dB over a wide frequency range from 52–61 GHz.